Investigating disparate approaches to refugee management in Europe and Africa - Widmann, Fiona (2021)
The global refugee population is at an all-time high and is expected to continue to rise in the near future. Recent crises in Europe as well as the refugee situation in Africa have once again highlighted the challenges in managing the world's refugees. While both regions are currently host to a significant number of refugees, their approaches to managing the situation appear to differ greatly. Therefore, this thesis sets out to investigate approaches to refugee management in Europe and Africa. In addition, it aims to find an answer to the question of how the chosen approach affects long-term refugee management and, in turn, the prospect of achieving durable solutions for refugees in the respective regions. Through an examination of the applicable laws, both internationally and regionally, as well as by consulting secondary sources, the ‘European approach' and the ‘African approach' to refugee management were identified. Furthermore, a closer look at two case studies, one from each region, provided more insight into how international and regional policies are translated in the domestic context, and what the ensuing prospects are for durable solutions. Deterrence appeared to be prevalent in both contexts, albeit arguably due to different circumstances. As significant shortcomings in achieving a dignified and rights-respecting approach to refugee management were identified, this thesis concludes with three recommendations